2016
DOI: 10.1111/jjns.12117
|View full text |Cite
|
Sign up to set email alerts
|

Relational coordination among home healthcare professions and goal attainment in nursing care

Abstract: The finding of this study suggest that well-coordinated professionals may fulfill client needs better than poorly coordinated professionals do. Future research is needed to determine whether similar results are obtained in individual clients using a well-validated goal attainment scale.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…For example, in the airline industry, relational coordination across 12 workgroups was associated with quality outcomes such as fewer passenger complaints, fewer late arrivals, and fewer baggage handling errors (Gittell, 2001). Similarly, subsequent studies in health care found relational coordination among interdisciplinary staff was positively associated with quality outcomes such as postoperative functional status, patient-reported quality of care and quality of life, family satisfaction with care, patient trust and confidence in their providers, and patient psychological well-being (Azar et al, 2017;Bae et al, 2010;Cramm et al, 2014;Cramm & Nieboer, 2012a, 2014aDeJesus, 2015;Gittell, 2002a;Gittell et al, 2000;Gittell et al, 2008;Havens et al, 2010;Noël et al, 2013;Romanow et al, 2018;Sakai et al, 2015;Sakai et al, 2016;Weinberg et al, 2007) as well as staff-reported quality of care (McDermott et al, 2017;McIntosh et al, 2014). These findings were further replicated in studies conducted in the pharmacy, professional services, higher education, and elder care industries (Alvarez, 2014;Drewery et al, 2016;Gittell et al, 2008;Hoos et al, 2012;Margalina et al, 2017;Skakon, 2014).…”
Section: Quality Outcomesmentioning
confidence: 93%
“…For example, in the airline industry, relational coordination across 12 workgroups was associated with quality outcomes such as fewer passenger complaints, fewer late arrivals, and fewer baggage handling errors (Gittell, 2001). Similarly, subsequent studies in health care found relational coordination among interdisciplinary staff was positively associated with quality outcomes such as postoperative functional status, patient-reported quality of care and quality of life, family satisfaction with care, patient trust and confidence in their providers, and patient psychological well-being (Azar et al, 2017;Bae et al, 2010;Cramm et al, 2014;Cramm & Nieboer, 2012a, 2014aDeJesus, 2015;Gittell, 2002a;Gittell et al, 2000;Gittell et al, 2008;Havens et al, 2010;Noël et al, 2013;Romanow et al, 2018;Sakai et al, 2015;Sakai et al, 2016;Weinberg et al, 2007) as well as staff-reported quality of care (McDermott et al, 2017;McIntosh et al, 2014). These findings were further replicated in studies conducted in the pharmacy, professional services, higher education, and elder care industries (Alvarez, 2014;Drewery et al, 2016;Gittell et al, 2008;Hoos et al, 2012;Margalina et al, 2017;Skakon, 2014).…”
Section: Quality Outcomesmentioning
confidence: 93%
“…Strong RC across organizations serving the same constituents enables participants to achieve higher quality outcomes more efficiently (27,28,31,32). A recent systematic review (29) identified several healthcare studies which positively associated relational coordination among interdisciplinary staff to quality outcomes including postoperative functional status, patient reported quality of care and quality of life, family satisfaction with care, patient trust and confidence with providers, and patient psychological well-being (27)(28)(29)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). Despite the growing evidence of relational coordination on patient and provider outcomes, only 14% of all RC findings were based on relational coordination between providers and their clients, including caregivers (29).…”
Section: Theorymentioning
confidence: 99%
“…In a prior series of studies [47,48], we incorporated the evidence-based practices of strengths-based learning [49,50], systematic observation [51], efficiency [48,52], and relationship-based teamwork [53,54] into a specific frontline staff huddling program known as the LOCK program. The LOCK program enables staff to (1) Learn from bright spots (focus on positive evidence of strengths); (2) Observe (collect data through systematic observation); (3) Collaborate in huddles (conduct frontline staff huddles); and (4) Keep it bite-size (limit activities to 5-15 min for efficiency) [48,55].…”
Section: Huddling and The Lock Programmentioning
confidence: 99%